The Effect of Emotional Intelligence on The Delinquency Behavior of Broken Home Adolescents - Sintha Pitaloka; Desi Sari; Zainun Mu'Tadin (Research Synergy Foundation, 2025)
Adolescents raised in disharmonious family environments often experience emotional dysregulation, increasing their vulnerability to delinquent behaviors such as minor crimes, rule violations, and social aggression. This study investigates the predictive role of emotional intelligence in mitigating delinquency among adolescents from broken-home families. Utilizing a culturally adapted questionnaire based on Goleman’s emotional intelligence framework and Hawkins' delinquency model, data were collected from 130 participants aged 12–21 years. The findings indicate that emotional intelligence significantly contributes to reducing delinquent behavior, accounting for 33.1% of the variance in this context. The study theoretically underscores the role of emotional regulation as a protective factor in developmental psychology. In practical terms, this study offers empirical evidence to support school- and family-based interventions aimed at strengthening adolescents’ emotional skills.